Acidic Microenvironment Up-Regulates Exosomal miR-21 and miR-10b in Early-Stage Hepatocellular Carcinoma to Promote Cancer Cell Proliferation and Metastasis - Tian, Xiao-Peng (Theranostics, 2019)
Rationale: The incidence of hepatocellular carcinoma is rising worldwide. It is predicted that nearly half of the early-stage hepatocellular carcinoma (E-HCC) patients will develop recurrence. Dysregulated pH, a hallmark of E-HCC, is correlated with poor prognosis. The acidic microenvironment has been shown to promote the release of exosomes, the membrane vesicles recognized as intercellular communicators associated with tumor progression, recurrence, and metastasis. We, therefore, aimed to identify exosomes induced by acidic microenvironment that may regulate E-HCC progression and to explore their mechanisms and clinical significance in E-HCCs. Methods: miRNA microarray analysis and LASSO logistic statistic model were used to identify the main functional exosomal miRNAs. Invasion and scratch assays were performed to examine the migration and invasion of HCC cells. Immunoblotting and immunofluorescence were employed to detect the epithelial-to-mesenchymal transition (EMT) in HCC cells. Chromatin immunoprecipitation (ChIP) was used to analyze the binding of HIF-1α and HIF-2α to promoter regions of miR-21 and miR-10b. Results: The acidic microenvironment in HCC was correlated with poor prognosis of patients. Exosomes from HCC cells cultured in the acidic medium could promote cell proliferation, migration, and invasion of recipient HCC cells. We identified miR-21 and miR-10b as the most important functional miRNAs in acidic HCC-derived exosomes. Also, the acidic microenvironment triggered the activation of HIF-1α and HIF-2α and stimulated exosomal miR-21 and miR-10b expression substantially promoting HCC cell proliferation, migration, and invasion both in vivo and in vitro. In E-HCC patients, serum exosomal miR-21 and miR-10b levels were associated with advanced tumor stage and HIF-1α and HIF-2α expression and were independent prognostic factors for disease-free survival of E-HCC patients. Most importantly, we developed a nano-drug to target exosomal miR-21 and/or miR-10b and examined its therapeutic effects against HCC in vivo. Conclusion: Our findings suggested that the exosomal miR-21 and miR-10b induced by acidic microenvironment in HCC promote cancer cell proliferation and metastasis and may serve as prognostic molecular markers and therapeutic targets for HCC.